Analysis Of Implementation Of Psak No. 1 Concerning Presentation Of Financial Statements At Pt Siantar Top Tbk - Early Armein; Diah Aryati Prihartini (Publisher Cv. Inara, 2021)
Purpose of this research in scientific writing is to find out whether PT Siantar Top Tbk has implemented its financial statements in accordance with PSAK no. 1. The data used by the author in this study are secondary data from the financial statements of PT Siantar Top Tbk in 2019 by downloading from the site www.idx.co.idwebsite. The data analysis method used in scientific writing is descriptive-comparative method. In this method the authors analyze and compare the financial statements of PT Siantar Top Tbk with PSAK No. 1. The results of this study show that there are still items that are not listed in the 2019 financial statements of PT Siantar Top Tbk. However, most of the 2019 financial statements of PT Siantar Top Tbk have implemented their financial statements in accordance with PSAK No. 1. Therefore, the implementation of the presentation of financial statements at PT Siantar Top Tbk must continue to be adjusted to PSAK No. 1. It is useful to be able to present complete financial statements in accordance with PSAK No. 1.